2017
DOI: 10.3892/etm.2017.5554
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and pathological characteristics of IgG4‑related interstitial lung disease

Abstract: IgG4-related interstitial lung disease (IgG4-RILD), which is characterized by increased IgG4 levels, IgG4+ plasma cell infiltration and irregular whorled fibrosis, is a recently described lung disorder that belongs to the group of systemic fibroinflammatory IgG4-related diseases (IgG4-RD). The aim of the present study was to improve the current knowledge regarding the specific clinical and histopathological characteristics of IgG4-RILD and to investigate its underlying immune mechanism in vivo. A total of 7 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
5
0
6
Order By: Relevance
“…In addition, there were no major differences in gender, age, IgG4 level, asbestosis or tobacco exposure between patterns. We confirm as reported from other series that lung involvement in IgG4-RD is heterogeneous [6,7,[11][12][13][14][17][18][19][20]. The discrepancies with other series between the frequencies of lung abnormalities observed suggests either a bias related to retrospective data collection, the lack of central imagery reviewing in some studies or a role of ethnic background.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, there were no major differences in gender, age, IgG4 level, asbestosis or tobacco exposure between patterns. We confirm as reported from other series that lung involvement in IgG4-RD is heterogeneous [6,7,[11][12][13][14][17][18][19][20]. The discrepancies with other series between the frequencies of lung abnormalities observed suggests either a bias related to retrospective data collection, the lack of central imagery reviewing in some studies or a role of ethnic background.…”
Section: Discussionsupporting
confidence: 76%
“…Studies have shown that neurotropic metastasis is related to the fusion of multiple genes in the host and gene mutations. There is no mention of the incidence-related genotype [ 18 ]. In lung cancer research, it was found that the CALCB gene polymorphism is associated with the incidence of lung cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-связанное склерозирующее заболевание, так называемая IgG4-связанная склерозирующая болезнь (IgG4-ССБ) впервые описана применительно к аутоиммунному панкреатиту (склерозирующему панкреатиту) [6]. Впоследствии описание этого заболевания включило в себя поражение других органов, в том числе желчного протока, слюнной железы, забрюшинного пространства и легкого [7]. Вне зависимости от пораженного органа, IgG4-ССБ демонстрирует общие клинико- При хирургическом вмешательстве из-за присутствия при воспалительной АБА плотного фиброзного сращения со структурами, прилегающими к брюшной аорте, рассечение затруднено, а непреднамеренное прокалывание аневризмы может привести к летальным осложнениям [4].…”
unclassified
“…До сих пор интерпретация воспалительной АБА неоднозначна. Некоторые исследователи рассматривают воспалительную АБА как крайний случай атеросклеротической АБА [5,7], тогда как другие предлагают видеть в воспалительной АБА аутоиммунный или инфекционный процесс [8,9]. Мы изучили воспалительную АБА с точки зрения IgG4-ССБ и пришли к выводу, что воспалительные АБА можно разделить на два типа: IgG4-связанные и IgG4-несвязанные случаи [9].…”
unclassified